Relations of microbiome characteristics to edaphic properties of tropical soils from Trinidad - de Gannes, Vidya; Eudoxie, Gaius; Bekele, Isaac; Hickey, William J. (Frontiers in Microbiology, 2015)
Understanding how community structure of Bacteria, Archaea and Fungi varies as a function of edaphic characteristics is key to elucidating associations between soil ecosystem function and the microbiome that sustains it. In this study, non-managed tropical soils were examined that represented a range of edaphic characteristics, and a comprehensive soil microbiome analysis was done by Illumina sequencing of amplicon libraries that targeted Bacteria (universal prokaryotic 16S rRNA gene primers), Archaea (primers selective for archaeal 16S rRNA genes) or Fungi (internal transcribed spacer region). Microbiome diversity decreased in the order: Bacteria > Archaea > Fungi. Bacterial community composition had a strong relationship to edaphic factors while that of Archaea and Fungi was comparatively weak. All communities were significantly more similar within soils, than they were between soils (ANOSIM p < 0.001); bacterial communities were 70-80% alike, while communities of Fungi and Archaea had 40-50% similarity. Communities differed in species turnover patterns, such that two soils with relatively similar bacterial communities could not be predicted to be similar in composition of Archaea or Fungi. Bacterial and archaeal diversity had significant (negative) correlations to pH, whereas fungal diversity was not correlated to pH. Edaphic characteristics that best explained variation between soils in bacterial community structure were: total carbon, sodium, magnesium and zinc. For fungi, the best variables were: sodium, magnesium, phosphorus, boron and C/N. Archaeal communities had two sets of edaphic factors of equal strength, one contained sulphur, sodium, and ammonium-N and the other was composed of clay, potassium, ammonium-N, and nitrate-N. Collectively, the data indicate that Bacteria, Archaea and Fungi did not closely parallel one another in community structure development, and thus microbiomes in each soil acquired unique identities. This divergence could in part refl